Comparative analysis of the relationship between of chronic periodontitis patients' compliance and clinical efficacy - Liu, Zong-xiang; Wang, Peng-lai; Du, Fang (Zhonghua kouqiang yixue zazhi, 2013)
To evaluate the effect of patients' compliance on clinical parameters in patients with chronic periodontitis during periodontal maintenance therapy period. Chronic periodontitis patients who had completed non-surgical periodontal basic treatment were incorporated into the periodontal maintenance therapy(PMT). Clinical examination was performed in the baseline and each quarterly recall, over 3-year period. Clinical parameters including number of teeth, probing depth(PD), attachment loss(AL) level and bleeding on probing(BOP), were recorded. According to the number of PMT visit, the patients were classified into three groups:regular complier(RC); erratic complier(EC); non-complier(NC). The final parameters(three years later) were obtained by outpatient follow-up and telephone interviews. The data were calculated for the pecentage of sites with PD 4-5 mm, PD ≥ 6 mm, AL 4-5 mm, AL ≥ 6 mm, BOP, and the number of tooth loss per patient and the rates of progression of periodontitis.Statistical analyses including ANO